Analisis Komparatif Penggunaan Drywall Partition Dibandingkan Dinding Bata Dalam Pembatas Ruangan Pada Bangunan Apartemen - Wiraguna, Sidi Ahyar (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
This research aims to analyze the comparison of the use of Drywall partition with conventional brick wall as room divider in apartment, focusing on efficiency, acoustic effectiveness, and structural load. The research method used is comparative with a quantitative approach, collecting data through surveys on apartment buildings that use both types of walls. The analysis was carried out through a comparison of costs, processing time, acoustic performance, and influence on structural loads. The results showed that the use of drywall partition provided significant advantages in terms of speed and cost reduction. Drywall partition is proven to be lighter in weight, reduces the structural load of the building, and speeds up the construction process. In terms of acoustics, drywall with proper insulation can match or even surpass the performance of brick walls in terms of soundproofing. The discussion also involves consideration of the sustainability and environmental impact of both materials. The conclusion of this research is that drywall partitions offer an efficient and effective alternative to room dividers in apartments, with the added benefits of easy installation and good acoustic performance. This research provides new insights for developers and architects in selecting optimal construction materials. Recommendations for future research include a deeper analysis of sustainability aspects and the choice of insulation materials to improve the acoustic performance of drywall.